Penggunaan Plastik Daur Ulang sebagai Kemasan Sabun Tangan Cair di Muhammadiyah Kramat Jati, Jakarta Timur (KMK No. HK.01.07-Menkes-382-2020 tentang Protokol Kesehatan bagi Masyarakat di Tempat dan Fasilitas Umum dalam Rangka Pencegahan Covid-19) - Marjan Miharja; Erwin Syahruddin; Saparuli Saparuli; Viktor Agung Pratama; Heru Mahendra; Ronal Saut; Hardian Hardian; Salamat Martua (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
The more single-use plastic is used, the higher the possibility of increasing plastic waste in the environment. Chemicals in plastics can endanger living things and humans, plastic / inorganic waste is still very minimal management. so that the use of used or recycled plastics as packaging or containers of liquid soap must be carried out to preserve the environment. To overcome this problem, Group 2 Community Service (PKM) STIH IBLAM will implement the use of recycled or used plastic bottles as hand soap packaging. Currently the Indonesian people are facing challenges that require human resources to adapt to the Corona Virus Disease 2019 (COVID-19) pandemic situation. Health, social and economic aspects must go hand in hand and support each other in order to achieve the expected goals. It is hoped that through the use of recycled or used plastic bottles as hand soap packaging it can help economically, socially, and maintain health during the COVID-19 pandemic. The results obtained from this activity are the use of recycled or used plastic bottles as hand soap packaging can reduce costs compared to using single-use plastic bottles and protect the environment from plastic waste which is difficult to decompose. Empowering the community for economic and social sustainability, as well as implementing health protocols in efforts to prevent and control COVID-19 in accordance with the Decree of the Minister of Health of the Republic of Indonesia Number Hk.01.07 / Menkes / 382/2020 concerning Health Protocols for Communities in Places and Public Facilities in the Context of Prevention and Control of Corona Virus Disease 2019 (Covid-19).